The vein book - Bergan, John J., 1927-2014 (Medicine and Dentistry 2007 : Subject Collection, 2007)
The Vein Book is a comprehensive reference on veins and venous circulation. In one volume it provides complete, authoritative, and up-to-date information about venous function and dysfunction, bridging the gap between clinical medicine and basic science. It is the single authoritative resource which consolidates present knowledge and stimulates further developments in this rapidly changing field. * Startling new treatment for venous thromboembolic disease * Details the condition of varicose veins, spider veins and thread veins and discusses treatment options * Radically effective treatment of leg ulcer * Clarification of the pathophysiology of Venous Insufficiency * Molecular mechanisms in the cause of varicose veins.